THE ISO 9000 STANDARD - Ivanova, Marija; Elksne, Maija; Meirāns, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The aim of the reports is determine the ISO 9000 standard development perspectives. Report consists of four chapters. In the first chapter is written the ISO 9000 standard developmental history. In the second chapter is described ISO 9000 standard edition and in the third chapter is take ISO 9000 standard edition comparison. In the fourth chapter is written the ISO 9000 standard perspectives